Phase II Trial of Eribulin in Patients With Metastatic Hormone Refractory Prostate Cancer: A Trial of the ECOG-ACRIN Cancer Research Group (E5805). (April 2019) - Stein, Mark N.; Chen, Yu-Hui; Carducci, Michael A.; Hudes, Gary R.; Lerma, Pauline M.; Tan, Winston W.; Dalune, Robert; Rowland, Kendrith M.; Kuzel, Timothy M.; DiPaola, Robert S.
Abstract : Background: Eribulin mesylate, a synthetic analog of halichondrin B, is a novel tubulin-binding agent that inhibits cancer cell proliferation at low-nanomolar levels. Methods: In a multicenter ECOG trial, patients with progressive metastatic CRPC, ECOG 0-2 were treated with eribulin 1.4 mg/m 2 as an IV bolus over 5 minutes on days 1 and 8 of a 21-day cycle. This noncomparative study stratified points to either a chemonaive (CN), prior-taxane (Tax) only, or 2 prior cytotoxic (TCx) chemotherapy arm. The trial was powered to detect a 50% PSA reduction using Consensus Criteria in at least 40% versus 20% (90% power, one-sided α=0.10) for the CN stratum and 25% versus. 10% (power 87%, one-sided α=0.10) for the Tax and TCx strata. Results: In total, 119 pts received treatment of which 116 were eligible for the primary response determination in this study. Median age 70 years (range, 45 to 88); median number of treatment cycles 4 (range, 1 to 20+); ECOG 0-1 90%. Confirmed PSA response rates (50% decline from baseline) were 29% (90% [18.2%, 41.2%]; P =0.20), 10% (90% [5.2%, 27.1%]; P =1.00), and 4% ([0.2%, 18.3%]; P =0.59) in the chemonaive stratum, the prior-taxane stratum, and the 2-prior-chemotherapy stratum, respectively. Median progression-free survival was 3.5 months (95% CI, 2.0, 5.9), 2.3 months (95% CI, 2.0, 2.9) and 3.7 months (95% CI, 2.1, 4.2) for the chemonaive stratum, the prior-taxane stratum and the 2-prior-chemotherapy stratum, respectively. Nonhematological toxicities of any grade (mainly grade 1 and 2) were fatigue (74%), neuropathy (40%), alopecia (39%), nausea (35%), and anorexia (34%). Common hematological toxicities were decreased leukocytes (75%), decreased neutrophils (72%), and decreased hemoglobin (66%). The most common grade ≥ 3 toxicities were decreased neutrophils (55%), decreased leukocytes (42%), sensory neuropathy (13%), and fatigue (11%). Overall, there was a 4% rate of febrile neutropenia. Conclusions: In summary, per the prespecified study endpoints, eribulin did not have adequate activity in chemotherapy naïve or chemotherapy pretreated patients with metastatic CRPC to support further study in this setting. Abstract : Supplemental Digital Content is available in the text.